An integral forward model of agency experience in thought and action - Oliver Lukitsch (Frontiers in Psychology)
Historically, Frith’s comparator model has been a seminal account of the sense of agency in thought and bodily action. According to this model, only thoughts and actions that are successfully predicted are experienced as agentive, thus providing a unified account of the sense of agency for mind and body. However, this unified model has since been rejected on the grounds that thinking and bodily action impose different constraints on the experience of agency and conscious prediction. While this is widely accepted, the predictive processing model of the sense of agency offers a new perspective that avoids previous arguments against a unified comparator model and paves the way for its reintroduction.